Penyuluhan Kesehatan Mental dalam Meningkatkan Prestasi Belajar Siswa Madrasah Aliyah Baytul Mukarromah Kabupaten Bone - Baharuddin; Andi Tahir; Bahtiar (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2025)
Student academic achievement is an indicator of academic success. However, behind the beautiful results, another important aspect is being forgotten: the mental health of students. This project aims to investigate the effect of mental health counseling on the academic performance of MA Baytul Mukarromah students. Based on the first observation, it was found that many students have difficulty managing stress and anxiety, which can affect their learning results. Therefore, it is hoped that this project can contribute to improving the quality of education at MA Baytul Mukarromah by providing relevant recommendations related to mental health education programs. The results of this project show that mental health counseling helps students in improving their learning outcomes. Counseling not only provides knowledge and skills, but also helps students develop self-awareness, increase their motivation to learn, and establish positive social relationships so that they are more aware of the importance of healthy mental health, which increases their academic performance for a better future.